Optimizing elderly management in improving functional independence - Kurniawan, Didi (Science Center Group, 2024)
The increasing aging population has heightened the need for effective management strategies that support functional independence among older adults. Functional independence, defined as the ability to perform daily activities autonomously, is crucial for maintaining quality of life in the elderly. This article discusses essential aspects of optimizing elderly management, emphasizing the role of gerontological nursing. Key strategies include addressing polypharmacy, promoting exercise interventions, implementing technological solutions such as smart home systems, and encouraging skill development. These approaches enable elderly individuals to sustain autonomy and reduce dependence on continuous supervision, thereby enhancing their dignity and well-being. By integrating these strategies, gerontological nursing can significantly contribute to improving the quality of life and independence among the elderly, meeting the demands of a growing demographic.